Development of Gamification-Based Online Learning Using Moodle - Nisaul Barakati Selirowangi; Novita Eka Chandra; Aditya Zulkarnaen Ali; Lady Lina Aulia; Abdullah Zahid; Megi Widiyah Triutami; Fiqiyah Biroudloh (STAI Miftahul Ula Nganjuk, 2022)
The Covid-19 pandemic has resulted in a change in the face-to-face learning process to online learning. But in the process, online learning is not always easy to do. Some of the problems in the implementation of learning from the internet network are not evenly distributed, the decrease in understanding ability and student learning outcomes, and also student saturation during the learning process. To overcome this, we need an online learning media based on gamification. Gamification is a learning process that is integrated with game design. This study aims to develop gamification-based online learning using Moodle media. The method used in this research is the research and development method. This research and development use the ADDIE model. The results of the validation test carried out by the validator developed were declared very valid, with a percentage of 87.5% by material validators and 93.75% by media validators. Based on the feasibility test that has been carried out, it is obtained a percentage of 90.5% with a feasible category. From the series of validation tests and trials, it can be stated that overall, the learning media developed are very valid and very suitable for use in online learning.